Effects of different breathing exercises and body positioning on diaphragmatic mobility among healthy subjects / Mohd Azrul Anuar Zolkafi - Zolkafi, Mohd Azrul Anuar (2015)
Introduction: Diaphragmatic Mobility (DM) is an essential component of breathing cycle and this varies accordingly to different positions. Traditionally, Breathing Exercises (BE) were encouraged in upright position to enhance its effectiveness. This study aimed to investigate the effect of Diaphragmatic Breathing Exercise (DBE) and Volume Oriented Device Incentive Spirometry (VODIS) exercise on DM in Semi-Fowlers (SF) and Right Lateral Decubitus (RLD) positions. Materials and Methods: This cross-over study involved 58 healthy male volunteers. All subjects performed DBE and VODIS in SF and RLD position in two different days. DM was evaluated using Real-Time Ultrasound B-mode in which transducer was placed to detect left portal vein and the readings were taken at a point of normal inspiration and deep inspiration. The best of three measurements was chosen for final interpretation. Results: The data was analyzed using Paired-T test and One-way ANOVA Repeated Measures. The results showed that the DM while performing quiet and deep inspiration in each position obtained significant value (p< .05). SF position accomplished to have greater DM compared to RLD position while performing VODIS (p< .05), however there was no significant difference obtained in DBE when compared between two different positions. Conclusion: Both types of breathing exercises produced greater DM when compared to quiet breathing. However, the VODIS promoted better result of DM than DBE in both positions. It has also been suggested that SF position offered better DM compared to RLD while performing these exercises.